2015
DOI: 10.1186/s13054-015-0760-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative renal near-infrared spectroscopy indicates developing acute kidney injury in infants undergoing cardiac surgery with cardiopulmonary bypass: a case–control study

Abstract: IntroductionAcute kidney injury (AKI) is a frequent complication after cardiac surgery with cardiopulmonary bypass in infants. Renal near-infrared spectroscopy (NIRS) is used to evaluate regional oximetry in a non-invasive continuous real-time fashion, and reflects tissue perfusion. The aim of this study was to evaluate the relationship between renal oximetry and development of AKI in the operative and post-operative setting in infants undergoing cardiopulmonary bypass surgery.MethodsIn this prospective study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 40 publications
(64 reference statements)
6
103
0
1
Order By: Relevance
“…To our knowledge, this is the first time that a relationship was identified between early measures of renal oximetry by NIRS and the development of AKI in very preterm infants. This result is consistent with that of Ruf et al [14] who demonstrated that prolonged low renal oximetry measured by NIRS during cardiac surgery in newborns was a reliable early parameter for predicting AKI, and even superior to conventional biochemical markers.…”
Section: Discussionsupporting
confidence: 82%
“…To our knowledge, this is the first time that a relationship was identified between early measures of renal oximetry by NIRS and the development of AKI in very preterm infants. This result is consistent with that of Ruf et al [14] who demonstrated that prolonged low renal oximetry measured by NIRS during cardiac surgery in newborns was a reliable early parameter for predicting AKI, and even superior to conventional biochemical markers.…”
Section: Discussionsupporting
confidence: 82%
“…Notably the rate of AKI is higher than our study population, in which only 3.8% of patients developed severe AKI [20]. Ruf et al, demonstrated a significant correlation between a calculated intraoperative renal NIRS score (which included the baseline value, the current value and the time in minutes, and calculated area under the curve) and the postoperative occurrence of AKI in infants after cardiac surgery.…”
Section: Discussionmentioning
confidence: 54%
“…Renal NIRS has been shown to be predictive of AKI in several small studies, using a series of complex equations or area under the curve (AUC) that do not have clinical relevance for predicting early AKI [19, 20]. One study reported a low renal oximetry of less than 50% for greater than 2 hours to be associated with AKI, and is the most clinically useful renal NIRS parameter assessed to date [21].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced mean arterial pressure and non-pulsatile renal blood flow during cardiopulmonary bypass (CPB) leads to renal ischemia and hypoxia, with resultant activation of apoptotic and necrotic pathways of tubule and endothelial cell death [25,26]. Direct and convincing evidence for low renal oxygenation during pediatric CPB has been obtained using near-infrared spectroscopy [2729]. Not surprisingly, the duration of CPB has been the single most consistently identified risk factor for pediatric CS-AKI [1].…”
Section: Incidence and Etiology Of Cardiac Surgery-associated Acutmentioning
confidence: 99%